Experimenting With Algorithms and Memory-Making: Lived Experience and Future-Oriented Ethics in Critical Data Science - Markham, Annette N.; Pereira, Gabriel (Frontiers in Big Data, 2019)
In this paper, we focus on one specific participatory installation developed for an exhibition in Aarhus (Denmark) by the Museum of Random Memory, a series of arts-based, public-facing workshops and interventions. The multichannel video installation experimented with how one memory (Trine’s) can be represented in three very different ways, through algorithmic processes. We describe how this experiment troubles the everyday (mistaken) assumptions that digital archiving naturally includes the necessary codexes for future decoding of digital artifacts. We discuss what’s at stake in critical (theory) discussions of data practices. Through this case, we offer an argument that from an ethical as well as epistemological perspective critical data studies can’t be separated from an understanding of data as lived experience.